2017
DOI: 10.18584/iipj.2017.8.3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to identify the factors that positively and negatively impacted on the employment experiences and trajectories of Indigenous Australians who are currently or were formerly employed by a research organisation in both remote and urban settings. The study design was an embedded mixed-methods approach. The first phase quantified staff uptake, continued employment, and attrition. Then interviews were conducted with 42 former and 51 current Indigenous staff members to obtain qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Related studies underscore these points. Reviewing the literature on Australian programmes designed to enhance the wellbeing of Aboriginal young people in out of home care, Lindstedt et al (2017) identified a striking absence of studies in this area. Similarly, in a review of the international literature on the involvement of Indigenous children in child protection services, Sinha et al (2021) noted that their study 'illustrates the limits of the academic literature in representing the knowledge and experience of Indigenous Peoples' (abstract).…”
Section: Introductionmentioning
confidence: 99%
“…Related studies underscore these points. Reviewing the literature on Australian programmes designed to enhance the wellbeing of Aboriginal young people in out of home care, Lindstedt et al (2017) identified a striking absence of studies in this area. Similarly, in a review of the international literature on the involvement of Indigenous children in child protection services, Sinha et al (2021) noted that their study 'illustrates the limits of the academic literature in representing the knowledge and experience of Indigenous Peoples' (abstract).…”
Section: Introductionmentioning
confidence: 99%